Contributions of Spanish Universities to research on Children and Media - Ruiz San Roman, José A.; Ortiz Sobrino, Miguel Ángel; Porto Pedrosa, Leticia (Anàlisi, 2013)
In the last years, the Spanish educational interest for the relationship between children and media has increased up to the point that this topic constitutes one of the main research lines of the universities in our territory. We find a development of the groups, observatories, laboratories and institutes from which works are obtained results that increase exponentially when those investigations are carried out in networks that allow organizations, until recently with no connection, to bring in contact with each other as well as share information with each other.Assuming how strong the interaction between the groups is, this work intends to offer a map of the research current status on children and the media at the Spanish universities, aiming to establish which are the main research lines of the centres, conclusions they have been reaching through their works and the trends and future perspectives of this interesting and wide field of study. Among the weak points, we conclude that Spanish studies still suffer from a lack of international dimension, which is not due to the fact that researchers don’t investigate about the situation of other countries, but because few of them take part in consortiums that allow to count on enough solvency to establish comparatives and roadmaps for the media and applicable regulations from supranational institutions, as European Union.